Mathematic Student Worksheets Based on The STAD Type Cooperative Learning Model to Improve Student Learning Acivities and Outcomes at MI Al Falah Probolinggo - Nurul Saila; Abdul Basit; Vita Rahmatun Nazilah; Ilmia; Afifa (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Learning is a process of interaction between educators, students and learning resources in a learning environment. The quality of learning depends on the quality of interaction between educators, students and learning resources in a learning environment. The problem that arises is the results of student observations when doing internships in class V MI Al Falah, in Mathematics it shows the minimum level of student learning mastery and the lack of positive student activity in learning. The results of interviews with fifth grade students informed that the learning model used by the teacher did not facilitate students to learn and the teacher did not have a student worksheet (LKS). The purpose of this service activity is to help class V MI Al Falah students increase their activities and learning outcomes in learning Mathematics, by implementing Mathematics learning using LKS with the STAD type cooperative learning model. The method of implementing this activity includes the following activities: preparation, implementation and evaluation. The result of this service activity is that learning Mathematics using LKS with the STAD type cooperative learning model in class V MI Al Falah helps students improve their activities and learning outcomes. The results of the questionnaire on student responses to service activities showed that 100% gave a positive response to Mathematics learning activities using LKS with the STAD type cooperative learning model